2022
DOI: 10.1186/s12889-022-12894-7
|View full text |Cite
|
Sign up to set email alerts
|

What is the impact of structural and cultural factors and interventions within educational settings on promoting positive mental health and preventing poor mental health: a systematic review

Abstract: Mental health (MH) difficulties are on the increase among children and young people (CYP). Evidence has shown that educational settings contain both risk and protective factors for MH. This review investigated which structural and cultural factors and interventions within educational settings promote positive MH and prevent poor MH in 4–18 year olds. Searches were conducted in PsychINFO, Embase, ERIC, ASSIA and British Education Index, and reference lists from key studies and relevant systematic reviews were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 97 publications
0
17
0
Order By: Relevance
“…Following this process, 10% of all references will be screened by two independent reviewers and references will be equally divided into sets and be distributed among all team members. Every set of references will be screened by one screener from the team during the title/abstract screening stage, with a random sample of 10% of the references reviewed by a second screener, following similar approaches in previous large-scale systematic reviews 50–52. Agreement rates for every pair of screeners will be recorded and reported as per cent agreement 53.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following this process, 10% of all references will be screened by two independent reviewers and references will be equally divided into sets and be distributed among all team members. Every set of references will be screened by one screener from the team during the title/abstract screening stage, with a random sample of 10% of the references reviewed by a second screener, following similar approaches in previous large-scale systematic reviews 50–52. Agreement rates for every pair of screeners will be recorded and reported as per cent agreement 53.…”
Section: Methodsmentioning
confidence: 99%
“…If the agreement rates between pairs of screeners were lower than 90% within the set of 10% randomly selected articles, all remaining articles in this set will be double-screened. Articles progressing to full-text screening will be retrieved and screened by a single screener, with a random sample of 10% reviewed by a second screener, again similar to previous approaches 50–52. If we identify more than one study, which includes the same or overlapping samples, we will prioritise studies using the following hierarchy: largest sample, longest follow-up, adjusted for highest number of confounders.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the theory of psychological development, psychologist, Erickson, proposed that childhood (6–11 years old) is the basic stage of individual physical and mental health development and the key to ensuring adult mental health [ 5 ]. However, studies at home and abroad have shown that the incidence of children’s mental health problems has become increasingly serious [ 6 ]. Compared with a decade ago, British teenagers had higher rates of depression and self-harm; parents reported higher levels of emotional difficulties, conduct problems, hyperactivity and peer problems, and less sleep [ 7 ].…”
Section: Introductionmentioning
confidence: 99%